Analisis Struktural Cerpen “Assyarru Bis-Syarri” Karya Abdul Fattah Shobri & Ali Umar - Habil Rahman Hakim; Shinta Fitria Utami (FKIP, Universitas Palangka Raya, 2024)
Literary work is the result of interpretation of the author's imagination in expressing phenomena that occur in human life. Literary works are composed of complex structures. The elements that make up the literary work relate to the others as a whole. Literary works are divided into several types, among these types there are short stories. In Arabic literature, short stories are called qissah qasirah. One of the famous Arabic short stories is